2014
DOI: 10.1371/journal.pone.0109418
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Cyr61 Induced Degeneration of Human Müller Cells in Diabetic Retinopathy

Abstract: The degeneration of Müller cells has been recognized to involve in the pathogenesis of diabetic retinopathy. However, the mechanism is not yet clear. This study is to explore the potential role of Cyr61, a secreted signaling protein in extracellular matrix, in inducing human Müller cell degeneration in diabetic retinopathy (DR). Twenty patients with proliferative diabetic retinopathy (PDR) and twelve non-diabetic patients were recruited for this study. Vitreous fluid was collected during vitrectomy surgery for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…You et al reported the occurrence of higher levels of CCN1 in the vitreous humor of patients with proliferative diabetic retinopathy (PDR) compared to patients without diabetes (5). This observation has been consistently confirmed by Zhang et al (9), Choi et al (10), and Zhou et al (11). Additionally, it was observed that the vascular activity in patients with PDR significantly affected the vitreous levels of CCN1 (11,12).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…You et al reported the occurrence of higher levels of CCN1 in the vitreous humor of patients with proliferative diabetic retinopathy (PDR) compared to patients without diabetes (5). This observation has been consistently confirmed by Zhang et al (9), Choi et al (10), and Zhou et al (11). Additionally, it was observed that the vascular activity in patients with PDR significantly affected the vitreous levels of CCN1 (11,12).…”
Section: Introductionmentioning
confidence: 81%
“…Additionally, it was observed that the vascular activity in patients with PDR significantly affected the vitreous levels of CCN1 (11,12). Zhou et al observed that CCN1 levels were significantly higher in patients with active PDR than in patients with quiescent PDR (11); additionally, Zhang et al found that vitreous CCN1 levels were higher in patients with PDR who had extensive neovascularization in the retina than in those with limited neovascularization (9). However, CCN1 levels were higher in the PDR group than in the control group, regardless of the PDR status (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Cysteine-rich angiogenic inducer 61 (Cyr61), belonging to the CCN family, is a 40 kD secreted extracellular matrix (ECM)- related signalling protein that can regulate cell proliferation, adhesion, differentiation and extracellular matrix production [ 7 9 ]. Cyr61 is maintained at a low level under normal conditions, but is usually elevated in various states of disease, such as colitis, rheumatoid arthritis, Graves’ orbitopathy, diabetic retinopathy and atherosclerosis [ 10 15 ]. Downregulation of Cyr61 expression in carotid balloon injury rats can mitigate the proliferation of vascular smooth muscle cells, thereby attenuating vascular intimal hyperplasia [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cysteine-rich angiogenic inducer 61 (Cyr61), belongs to CCN family, is a 40 kD secreted extracellular matrix (ECM)-related signaling protein that can regulate cell proliferation, adhesion, differentiation and extracellular matrix production [7][8][9]. Cyr61 is maintained at a low level under normal conditions, but is usually elevated in various status of disease, such as colitis, rheumatoid arthritis, Graves' orbitopathy, diabetic retinopathy and atherosclerosis [10][11][12][13][14][15]. Moreover, inhibition of Cyr61 expression in carotid balloon injury rats can mitigated the proliferation of vascular smooth muscle cells, thereby attenuating vascular intimal hyperplasia [16].…”
Section: Introductionmentioning
confidence: 99%